Using routine Haemophilia Joint Health Score for international comparisons of haemophilia outcome: standardization is needed. (14th July 2015) - Nijdam, A.; Bladen, M.; Hubert, N.; Pettersson, M.; Bartels, B.; van der Net, J.; Liesner, R.; Petrini, P.; Kurnik, K.; Fischer, K.
Abstract : Introduction: Haemophilia Joint Health Score (HJHS) is the most sensitive validated score for physical examination of joint health in haemophilia. HJHS performed at regular intervals can be used for clinical monitoring as well as for comparative outcomes research. Aim: To determine whether routinely collected HJHS could be used to compare outcome of three different prophylactic regimens in children with severe haemophilia A (primary) and which parameters caused variability in HJHS (secondary). Methods: International retrospective observational multi‐centre study comparing routine HJHS in 127 children with severe haemophilia A born from 1995 to 2009, from London, Stockholm and Utrecht centres. Patient and treatment data were collected from the European Paediatric Network for Haemophilia Management registry and patient files. The independent effects of regimens, physiotherapists, age and inhibitor status on HJHS were explored, using multivariable regression analysis. Results: Prophylaxis varied across participating centres, with differences in initial frequency of infusions (1× per week vs. 3× per week), age at reaching infusions ≥3× per week, and dose kg −1  week −1 at HJHS assessment. Evaluation at median age of 11 years showed an illogical association of HJHS with treatment regimen: the least intensive regimen had the lowest HJHS. The HJHS increased with age and history of inhibitor, as expected (internal validity). But the comparison of prophylactic regimens was obscured by systematic differences in assessment between physiotherapists, both within and between centres. Conclusion: Inter‐physiotherapist discrepancies in routine HJHS hamper comparison of scores between treatment regimens. For multi‐centre research, additional inter‐observer standardization for HJHS scoring is needed.